2000
DOI: 10.1080/109158100750058749
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Protection Against Chemically Induced Hepatotoxicity

Abstract: The protective effect of putrescine (a polyamine) on chemically induced hepatotoxicity in male Sprague-Dawley rats was assessed by mortality, clinical pathological changes (specifically alanine aminotransferase and aspartate aminotransferase activities), and liver histopathological changes. A reduction in hepatotoxicant-induced mortality by 20% to 25% was observed when putrescine (100 mg/kg/day) was administered intraperitoneally for 3 days prior to hepatotoxicant administration (either carbon tetrachloride or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…As in our experiments, previous experimental studies have shown that CC14 administered at different dosages vŸ different routes increased significantly serum AST (1,6,10,13,18,19,21), ALT (1,6,10,13,18,19,21,27,28), total and conjugated bilirubin (13), ALP (13) and ~-GT (i3) levels, and decreased urea (8,25,32), total protein (13) and albumin (13,21) levels. However, there is a controversy about the effect of CC14 on serum creatinine level.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As in our experiments, previous experimental studies have shown that CC14 administered at different dosages vŸ different routes increased significantly serum AST (1,6,10,13,18,19,21), ALT (1,6,10,13,18,19,21,27,28), total and conjugated bilirubin (13), ALP (13) and ~-GT (i3) levels, and decreased urea (8,25,32), total protein (13) and albumin (13,21) levels. However, there is a controversy about the effect of CC14 on serum creatinine level.…”
Section: Discussionsupporting
confidence: 66%
“…The effects of such agents as colchicine (10), putrescine (18), ginkgo biloba (4) and black tea (12) extracts, antioxidant vitamins (C and E), seienium (34), somatostatin and octreotide (7) against toxic effects of CCI4 have been investigated.…”
mentioning
confidence: 99%